High prevalence of ArmA-16S rRNA methyltransferase among aminoglycoside-resistant Klebsiella pneumoniae bloodstream isolates. Issue 12 (20th December 2022) - Isler, Burcu; Falconer, Caitlin; Vatansever, Cansel; Özer, Berna; Çınar, Güle; Aslan, Abdullah Tarık; Forde, Brian; Harris, Patrick; Şimşek, Funda; Tülek, Necla; Demirkaya, Hamiyet; Menekşe, Şirin; et al.
Abstract : Introduction. Aminoglycosides are used for the treatment of carbapenemase-producing Klebsiella pneumoniae (CPK) infections. 16S rRNA methyltransferases (RMTs) confer resistance to all aminoglycosides and are often cocarried with NDM. Hypothesis/Gap Statement. There is a dart of studies looking at the aminoglycoside resistance mechanisms for invasive CPK isolates, particularly in OXA-48 endemic settings. Aim. We aimed to determine the prevalence of RMTs and their association with beta lactamases and MLSTs amongst aminoglycoside-resistant CPK bloodstream isolates in an OXA-48 endemic setting. Methodology. CPK isolates ( n =181), collected as part of a multicentre cohort study, were tested for amikacin, gentamicin and tobramycin susceptibility using custom-made sensititre plates (GN2XF, Thermo Fisher Scientific). All isolates were previously subjected to whole-genome sequencing. Carbapenemases, RMTs, MLSTs and plasmid incompatibility groups were detected on the assembled genomes. Results. Of the 181 isolates, 109(60 %) were resistant to all three aminoglycosides, and 96 of 109(88 %) aminoglycoside-resistant isolates carried an RMT (85 ArmA, 10 RmtC, 4 RmtF1; three isolates cocarried ArmA and RmtC). Main clonal types associated with ArmA were ST2096 (49/85, 58 %) and ST14 (24/85, 28 %), harbouring mainly OXA-232 and OXA-48 +NDM, respectively. RmtC was cocarried with NDM (5/10) on ST395, and NDM +OXA-48 or NDM +KPC (4/10) on ST14, ST15 and ST16. All RMT producers also carried CTX-M-15, and the majority cocarried SHV-106, TEM-150 and multiple other antibiotic resistance genes. The majority of the isolates harboured a combination of IncFIB, IncH and IncL/M type plasmids. Non-NDM producing isolates remained susceptible to ceftazidime-avibactam. Conclusion. Aminoglycoside resistance amongst CPK bloodstream isolates is extremely common and mainly driven by clonal spread of ArmA carried on ST2096 and ST14, associated with OXA-232 and OXA48 +NDM carriage, respectively.